2014
DOI: 10.3354/esr00584
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for recovery in the population of sperm whale bulls off Western Australia, 30 years post-whaling

Abstract: The global sperm whale Physeter macrocephalus population has been protected from large-scale commercial whaling for > 25 yr, yet there is no clear evidence of recovery in any heavily exploited stock. This may indicate that whaling has long-term demographic effects on this species or that other endogenous or exogenous processes are inhibiting population growth. This study investigates the status of mature sperm bulls off Albany, Western Australia, a population reduced through whaling by 74% between 1955 and 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…The survey found sperm whales in the Perth Canyon, Albany Canyon group, and the historical New Holland whaling grounds. Previous aerial surveys and passive acoustic studies have identified sperm whales in the Perth Canyon region (Bannister, 1968;Mccauley et al, 2004) and Albany Canyon group (Carroll et al, 2014). However, the RV Odyssey results provide the first detailed acoustic "presence" data of sperm whales primarily distributed along the continental shelf, submarine canyon and ridges.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The survey found sperm whales in the Perth Canyon, Albany Canyon group, and the historical New Holland whaling grounds. Previous aerial surveys and passive acoustic studies have identified sperm whales in the Perth Canyon region (Bannister, 1968;Mccauley et al, 2004) and Albany Canyon group (Carroll et al, 2014). However, the RV Odyssey results provide the first detailed acoustic "presence" data of sperm whales primarily distributed along the continental shelf, submarine canyon and ridges.…”
Section: Discussionmentioning
confidence: 75%
“…The study identified the critical areas for sperm whales are submarine canyons found offshore of Albany and Perth. Using ship-based and aerial methods to study and monitor species such as sperm whales is costly, as weather in regions such as WA is variable offshore (Carroll et al, 2014) and because of this and other logistical reasons, monitoring often does not occur for cetaceans in these areas (Donovan, 2005). The dive cycle and vocalizations produced by sperm whales make them a suitable species with which to use passive acoustic techniques for monitoring habitat use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatiotemporal distribution of sperm whales in the western North Atlantic and elsewhere around the world has been shaped in significant and complex ways by the long history of human exploitation of the species, which dramatically reduced their populations. To date, there is little evidence that sperm whale populations have recovered since the cessation of large-scale commercial whaling more than 30 yr ago (Carroll et al 2014, and the species is internationally listed as Vulnerable on the IUCN Red List of Threatened Species. Understanding the contemporary seasonal distribution of sperm whales has important implications for management and conservation, as they still face a wide range of human-caused stressors, including entanglement in fishing gear, ship strikes, and exposure to anthropogenic noise (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…After almost a century of large-scale commercial whaling that continued until the 1980s, the sperm whale stock underwent a global population decline, which is currently slowly recovering from depletion. In some areas though, subpopulations are not recovering and even continue to decline, likely due to bycatch in driftnets and chemical and noise pollution factors (Carroll et al 2014). Previous work has shown that the behavior of sperm whales can be altered in response to naval sonar exposure , Sivle et al 2012, Isojunno et al 2016).…”
Section: Introductionmentioning
confidence: 99%